Experimental Rnomics : : Towards The Identification And Characterization Of Non-Protein-Coding Ribonucleic Acids In Pathogenic Agents, Salmonella Typhi - Zakaria, Robaiza (2009)
This thesis focused on the experimental identification of small npcRNAs from Salmonella enterica serovar Typhi (S. Typhi), the aetiological agent of typhoid fever. Tesis ini memberikan tumpuan ke atas pengenalpastian npcRNA secara eksperimental daripada bakteria patogenik Salmonella enterica serovar Typhi (S. Typhi), penyebab penyakit demam kepialu.